On the effect of temperature coefficient of surface tension on shape and geometry of weld beads in hot wire gas tungsten arc welding process. (2018) - Rajesh Kannan, P.; Muthupandi, V.; Devakumaran, K.
Abstract: S304HCu stainless steel is inevitable materials in super heater and reheater tubes in steam power boiler industries. The major challenge in welding of T92 steel and S304HCu stainless steel is the selection of the appropriate filler wire and establishing welding procedures especially in dissimilar welding such that the weld joints meet the service requirements at high temperatures. This present work is aimed to study the effect of welding current and wire feed rate on weld bead geometry produced with hot wire gas tungsten arc welding (HW-GTAW) process using different filler wires of 0.8mm diameter viz., ERNiCrFe-7A (IN 52M) and ERNiCrCoMo-1 (IN 617) on S304HCu stainless steel tubes. These weld bead depositions were made at hot wire current of 30A with two different welding currents viz., 130A and 110A at a constant wire feed rate and travel speed. From the results, it is established that temperature distribution and the presence of surface active elements are the causes for the formation of weld beads in different shapes.